2022
DOI: 10.5539/jas.v14n9p47
|View full text |Cite
|
Sign up to set email alerts
|

Residual Herbicides and Cover Crops Interactions for Soybean Weed Control

Abstract: Residual herbicides and cover crops are important tools inside an integrated weed management program. The straw produced in crop rotation can interacts with herbicides. The aim of this study was to evaluate the interaction of diclosulam, sulfentrazone, imazethapyr, flumioxazin, s-metolachlor and pyroxasulfone with black oat, cereal rye, common vetch and oilseed radish cover crops and it´s reflection on weed control and soybean production. Were evaluated the biomass production of cover crops and its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Commercial post-emergence herbicides for the protection of agricultural crops from weeds are nowadays an essential way to ensure optimal growth and yield of soybean crops [28]. Although weed control management uses methods and active substances that usually do not influence the growth of non-target species, herbicide application is reported to have an influence on agricultural crops [28,[45][46][47]. Based on Croatian legislation, the last treatment with the recommended combination of herbicides should be by the end of the emergence of the third trefoils (V3) and before the emergence of the flowers (R1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial post-emergence herbicides for the protection of agricultural crops from weeds are nowadays an essential way to ensure optimal growth and yield of soybean crops [28]. Although weed control management uses methods and active substances that usually do not influence the growth of non-target species, herbicide application is reported to have an influence on agricultural crops [28,[45][46][47]. Based on Croatian legislation, the last treatment with the recommended combination of herbicides should be by the end of the emergence of the third trefoils (V3) and before the emergence of the flowers (R1).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, non-targeted species usually have tolerance to specific herbicides due to their fast-metabolic degradation [50][51][52]. Moreover, several recent investigations confirmed that herbicide treatments have little or no effect on final yield production of soybeans [47,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the control provided by straw and application of pre-emergent herbicides was enough to ensure maximum soybean productivity, even without other interventions in the post-emergence of the crop. In this area, with a weed community mostly composed of monocot species, no (Duarte et al, 2021;Roncatto et al, 2022).…”
Section: Data Collection and Analysismentioning
confidence: 99%